Dr George Paterson Barton QC 1925–2011 - Committee, VUWLR (Victoria University of Wellington Law Review, 2012)
This article serves as a foreword for this issue of the Victoria University of Wellington Law Review celebrating the life of Dr George Barton QC, who served as a member, Professor, and Dean of the Faculty of Law. This issue presents a wide selection of papers written by colleagues and friends of the life and the law of George Barton.